2003
DOI: 10.1074/jbc.m304193200
|View full text |Cite
|
Sign up to set email alerts
|

The Digestive Food Vacuole of the Malaria Parasite Is a Dynamic Intracellular Ca2+ Store

Abstract: The acidic food vacuole of Plasmodium falciparum has been the subject of intense scientific investigation in the 40 years since its role in the digestion of host hemoglobin was first suggested. This proposed role has important implications for the complex host-parasite inter-relationship and also for the mode of action of several of the most effective antimalarial drugs. In addition, adaptive changes in the physiology of this organelle are implicated in drug resistance. Here we show that in addition to these f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
66
0
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 26 publications
6
66
0
2
Order By: Relevance
“…Ca 2+ ions have also been suggested as a potential modifier of parasite drug resistance in the P. falciparum DV [34]. Therefore, we measured the steady-state Ca 2+ content of lysosomes in HEK293 cells expressing PfCRT isoforms (Fig.…”
Section: Pfcrt Expression Did Not Affect Lysosomal Ca 2+ Releasementioning
confidence: 99%
“…Ca 2+ ions have also been suggested as a potential modifier of parasite drug resistance in the P. falciparum DV [34]. Therefore, we measured the steady-state Ca 2+ content of lysosomes in HEK293 cells expressing PfCRT isoforms (Fig.…”
Section: Pfcrt Expression Did Not Affect Lysosomal Ca 2+ Releasementioning
confidence: 99%
“…However, a continuous net uptake of Ca 2ϩ occurs as the parasite matures (10), which has been attributed to an increased Ca 2ϩ permeability of the host erythrocyte plasma membrane (11,12). The parasite's cytoplasm is thought to contain a low free [Ca 2ϩ ] i of ϳ100 nM (13), similar to that of other eukaryotic cells (14), although quantitative determinations are controversial, ranging from 50 to 700 nM (15,16). Early during intraerythrocytic development, high concentrations of Ca 2ϩ appear to accumulate transiently in the parasitophorous vacuole (17), which separates the parasite from the erythrocyte cytosol.…”
mentioning
confidence: 99%
“…Early during intraerythrocytic development, high concentrations of Ca 2ϩ appear to accumulate transiently in the parasitophorous vacuole (17), which separates the parasite from the erythrocyte cytosol. Other subcellular organelles considered to serve as intracellular Ca 2ϩ stores are the parasite's endoplasmic reticulum (ER), 1 the food vacuole (16,18), and the acidocalcisomes (15, 18 -22).…”
mentioning
confidence: 99%
“…It has been reported that P. falciparum and P. chabaudi extrude H + to the extracellular medium by a Na + independent mechanism (Saliba & Kirk 1999). Other mechanisms for pH regulation described in malaria parasites may involve the V-H + -ATPase and the V-H + -PPase in acidocalcisomes (Marchesini et al 2000, McIntosh & Vaidya 2002, Saliba et al 2003, Biagini et al 2003. We have reported the existence of Ca 2+ pools in the acidic compartment of rodent as well as human malaria parasites as a possible mechanism for the regulation of calcium concentration in these parasites , Passos & Garcia 1998.…”
mentioning
confidence: 99%